2021
DOI: 10.3201/eid2710.210080
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Antigen Test for SARS-CoV-2 in Asymptomatic College Students

Abstract: We used the BinaxNOW COVID-19 Ag Card to screen 1,540 asymptomatic college students for severe acute respiratory syndrome coronavirus 2 in a low-prevalence setting. Compared with reverse transcription PCR, BinaxNOW showed 20% overall sensitivity; among participants with culturable virus, sensitivity was 60%. BinaxNOW provides point-of-care screening but misses many infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 4 publications
1
24
0
Order By: Relevance
“…Across other studies, BinaxNOW sensitivity varied between 64.4% and 96.5% among symptomatic persons ( 6 , 8 , 10 13 ) and between 20.0% and 70.2% among asymptomatic participants ( 9 , 14 ). Several factors may contribute to variability in test performance, including differences in population characteristics, the timing during disease course, test operator training ( 7 ), and methodological differences, such as the comparator rRT-PCR assay, specimen type, and collection method.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Across other studies, BinaxNOW sensitivity varied between 64.4% and 96.5% among symptomatic persons ( 6 , 8 , 10 13 ) and between 20.0% and 70.2% among asymptomatic participants ( 9 , 14 ). Several factors may contribute to variability in test performance, including differences in population characteristics, the timing during disease course, test operator training ( 7 ), and methodological differences, such as the comparator rRT-PCR assay, specimen type, and collection method.…”
Section: Discussionmentioning
confidence: 75%
“…Prior studies ( 6 14 ) have examined BinaxNOW antigen test performance; however, detailed data on the association of antigen test performance compared to rRT-PCR and viral culture by key epidemiologic characteristics, such as symptom and known exposure status, timing during infection, and demographic variables, are limited. An earlier brief report ( 15 ) analyzing these data showed high specificity for BinaxNOW but low sensitivity in specimens from either symptomatic (64.2%) or asymptomatic persons (35.8%) and showed improved sensitivity compared to rRT-PCR when limiting the analysis to culture-positive specimens.…”
Section: Introductionmentioning
confidence: 99%
“…However, 2 studies with IFU-conforming testing procedure on NP or AN/MT sample, still showed a low sensitivity. This quite likely results from the on average low viral load in 1 study [49], and the asymptomatic study population in the other [175]. On the contrary, compared to the other studies unusual high sensitivity was found in studies where average viral load was high [45, 84, 144, 145] or participants were mainly within the first week of symptom onset [42, 54, 135].…”
Section: Discussionmentioning
confidence: 98%
“…The European Centers for Disease Control and Prevention recommend that antigen tests should not be used for the screening of asymptomatic patients if the prevalence is <10% [ 60 ]. The sensitivity of antigen tests using self-collected specimens, such as saliva or ANS, is even lower [ 63 - 67 ].…”
Section: Antigen Testmentioning
confidence: 99%